2020
DOI: 10.1098/rsos.201520
|View full text |Cite
|
Sign up to set email alerts
|

Credibility of preprints: an interdisciplinary survey of researchers

Abstract: Preprints increase accessibility and can speed scholarly communication if researchers view them as credible enough to read and use. Preprint services do not provide the heuristic cues of a journal's reputation, selection, and peer-review processes that, regardless of their flaws, are often used as a guide for deciding what to read. We conducted a survey of 3759 researchers across a wide range of disciplines to determine the importance of different cues for assessing the credibility of individual preprints and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…This occurs despite the fact that ECRs are often on the leading edge of publishing trends and positioned to provide key insight for journals navigating quickly changing editorial waters. For example, ECRs are more likely than their senior colleagues to view the emerging practice of posting 'pre-prints' prior to manuscript submission favourably (Soderberg et al, 2020); and ECRs are six times more likely to make their data public (Campbell et al, 2019). Here, we argue that ECR editorial fellowships designed around two-way knowledge V I E W P O I N T…”
mentioning
confidence: 81%
“…This occurs despite the fact that ECRs are often on the leading edge of publishing trends and positioned to provide key insight for journals navigating quickly changing editorial waters. For example, ECRs are more likely than their senior colleagues to view the emerging practice of posting 'pre-prints' prior to manuscript submission favourably (Soderberg et al, 2020); and ECRs are six times more likely to make their data public (Campbell et al, 2019). Here, we argue that ECR editorial fellowships designed around two-way knowledge V I E W P O I N T…”
mentioning
confidence: 81%
“…Given that preprint servers conduct only light screening of manuscripts, it is understandable that some are concerned about the reliability and trustworthiness of preprints. A 2019 survey of almost 4,000 researchers across a wide range of disciplines concluded that preprints can improve and accelerate scholarly communication if researchers view them as credible enough to read and use (Soderberg et al, 2020). By adding indicators of transparency/openness of research content and process (e.g.…”
Section: Reliability and Credibilitymentioning
confidence: 99%
“…32 For example, the peer-reviewed study on preprint credibility published by Nosek and co-workers in 2020 included the following statement: "The final survey included questions in four categories: engagement information, the importance of cues for credibility, credibility of service characteristics, and demographics (see https://osf.io/4qs68/ for the full version of the questionnaire". 33 The link https://osf.io/4qs68/ directs readers to a preprint entitled "Credibility of Preprints Survey/Materials" 34 that in its turn includes all the methodology details on the survey of 3,759 researchers about their perceptions of the importance of different cues for assessing the credibility of preprints.…”
Section: Immediate Publishing Of Reproducible Researchmentioning
confidence: 99%